Teen pregnancy: Experience at the National Hospital Cayetano Heredia. 1992-1994. - Salvador, Jorge (2015)
Prospective longitudinal cohort type study done at the obstetrical service of Cayetano Heredia National Hospital, 1992 to December 1994 to determine the caracteristics and risks of deliveries in adolescents. Reviewing the informatic system data bank, we determined that 15% of deliveries attended were in adolescents; 52% lacked prenatal complications, especially premature rupture and preeclampsia. Abdominal delivery occurred between 14 and 24 %, especially due to cephalopelvic disproportion, breech presentation and preeclampsia. Height in less than 16 years girls was smaller than in the other groups (p<0,05). Risks for early adolescents were unstable union, nulliparity, preeclampsia, cephalopelvic disproportion, low birtweight and prematurity. For late adolescents, unstable union, nulliparity, preeclampsia and cephalopelvic disproportion.